UJI AKTIVITAS ANTIBAKTERI KOMBINASI BIJI PEPAYA (Carica Papaya L) DAN DAUN PANDAN WANGI (Pandanus Amaryllifolius Roxb) TERHADAP Escherichia Coli - Iswandi; Siti Nur Afifah; Nurfitriyawatie (Jurnal Farmasi IKIFA, 2024)
Carica Papaya L seeds contain various compounds such as tocopherols, terpenoids, alkaloids, carpains and flavonoids. Carica Papaya L seeds have been studied to have antibacterial activity by damaging the integrity of bacterial cell membranes. Fragrant pandan (pandanus amaryllifolius Roxb) is widely known to have benefits such as antidiabetic, anticancer, antioxidant and antibacterial. This study aims to determine the activity of a combination of Carica Papaya L seeds and pandanus amaryllifolius Roxb leaves against Escherichia coli. The method used was Kirby – Bauer diffusion with concentration an extract ratio of 1:1, 1:2 and 2:1 using a blank paper disk, and a paper disk as a positive control containing 5µl ciprofloxacin. Carica Papaya and Pandanus Amaryllifolius.Roxb extracts have antibacterial activity against Eschericia coli. Concentration 1:2 has better activity as proven to have the highest inhibition zone 7.7 mm.